High-Pressure Microfluidic Crystallization of Active Pharmaceutical Ingredients Using a Gas Antisolvent Process - Arora, Deepali (Curtin University, 2021)
The work focused on the development of a novel microfluidic platform that enables continuous pharmaceutical crystallization in an efficient and reproducible manner using pressurized carbon dioxide. Excellent control over the pharmaceutical crystal shape, size and structure was achieved. This is a step forward in the process intensification of existing crystallization methods. It combines greener processes and flexible microtechnology to improve the bioavailability and therapeutic efficiency of pharmaceutical products.